A Broadband Wireless MIMO-OFDM Demonstrator. Design and Measurement Results - Ventura, Lluis M.; Nieto, Xavier; Gregoire, Jean-philippe; de Win, Wouter; Lugil, Nico (2006 IEEE 17th International Symposium on Personal, Indoor and Mobile Radio Communications, 2006)
In this paper, a broadband wireless 4times4 multiple-input multiple-output (MIMO) space-time-block-coded (STBC) OFDM demonstrator is presented. A general description of the hardware architecture of the testbed is shown. The FPGA and DSP-based algorithms implemented at the transmit and receive sides are defined and compared to traditional single-antenna designs. A new physical layer for multiple antenna systems based on an extension of the IEEE 802.11a/g is introduced. Real measurement results over different spatial diversity schemes are finally presented to illustrate the effective gains obtained from the use of multiple transmit and receive antennas in a multicarrier system